2016
DOI: 10.1002/1873-3468.12500
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of circular RNAs in zebrafish

Abstract: Edited by Tamas DalmayCircular RNA (circRNA), a class of RNAs with circular structure, has received little attention until recently, when some new features and functions were discovered. In the present study, we sequenced circRNAs in zebrafish (Danio rerio) and identified 3868 circRNAs using three algorithms (find_circ, CIRI, segemehl). The analysis of microRNA target sites on circRNAs shows that some circRNAs may function as miRNA sponges. Furthermore, we identified the existence of reverse complementary sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 37 publications
2
68
2
Order By: Relevance
“…Putative circRNAs identified in our study had up to ∼50-fold lower abundance compared to previous studies 3,6,12 , likely reflecting differences in species, RNA preparation, cell types, choice of algorithm software for circRNA prediction 22 , or the nature of our samples. We speculated the last scenario to be the most likely, as we used much smaller quantities of material isolated in a compartment-and tissue-specific fashion from the in vivo context of developing embryos instead of abundant whole cell lysates from large quantities of cultured cells or whole tissue from embryos.…”
Section: /17contrasting
confidence: 70%
See 1 more Smart Citation
“…Putative circRNAs identified in our study had up to ∼50-fold lower abundance compared to previous studies 3,6,12 , likely reflecting differences in species, RNA preparation, cell types, choice of algorithm software for circRNA prediction 22 , or the nature of our samples. We speculated the last scenario to be the most likely, as we used much smaller quantities of material isolated in a compartment-and tissue-specific fashion from the in vivo context of developing embryos instead of abundant whole cell lysates from large quantities of cultured cells or whole tissue from embryos.…”
Section: /17contrasting
confidence: 70%
“…The biogenesis of circRNAs has been shown to be modulated by circularisation "signals" such as complementary sequences and/or secondary structures, which are embedded within the introns that flank circularised exons 7,8,9 . In terms of circRNA function, it has been suggested that they may function as miRNA sponges 10,3,11 , a finding further supported by a recent study of circRNAs in adult zebrafish 12 . CircRNAs can also regulate transcription of their parental genes in the nucleus 13 , and, in certain cases, may be translated into proteins 14 .…”
mentioning
confidence: 77%
“…In our study, we found approximately 9.24-16.58% contained reverse complement sequences. Rate of utilization of the intron-pairing-driven model in cotton is greater than in zebrafish (2.64%) [8], O. sativa (6.2%) and A. thaliana (0.3%) [21], but is lesser than in humans, which 40% of human circRNAs which have ALU in flanking sequences [16], indicating complementarity of sequences is clearly not the critical feature of plant circRNA circularization; the biogenesis of circRNA may be different in human and plants.…”
Section: Biogenesis Mechanism Of Plant Circrnamentioning
confidence: 97%
“…With technological breakthroughs in high-throughput deep sequencing, large numbers of circRNAs have been recently found in human [11, 20, 40], mouse [11, 20], nematodes [11, 41], zebrafish [42], Drosophila [43], protists [44] and plants [44]. Additionally, evolutionarily conserved sequences of circRNAs have been found.…”
Section: Properties Of Circrnas In Eukaryotic Cellsmentioning
confidence: 99%